2017
DOI: 10.1111/jen.12402
|View full text |Cite
|
Sign up to set email alerts
|

A new method of deploying entomopathogenic fungi to control adult Aedes aegypti mosquitoes

Abstract: A new system for deployment of fungus-impregnated black cloths was tested against and 48 hr to a PET trap with adhesive film + black cloth resulted in higher rates of trapped mosquitoes (38.6% and 68%, respectively) when compared with adhesive film only (6% and 12.6%, respectively). Both fungal species were effective at reducing survival rates when mosquitoes were exposed to traps for 24 hr or 48 hr. Lower exposure times did not significantly alter survival rates when compared to controls. The results showed t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0
3

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 20 publications
0
10
0
3
Order By: Relevance
“…Particular attention has been paid to fungal species belonging to the genera Lagenidium, Coelomomyces, Entomophthora, Culicinomyces, Beauveria, and Metarhizium for their power to reduce mosquito populations, but unfortunately, none of them have been specifically adapted as larvicidal agents against important vector species [109][110][111], even transgenic ones [112]. Application to surfaces on which mosquitoes land or need to pass through, such as fungus-impregnated cloths around bed nets, attractive bait stations, and adult mosquito traps and PET traps, show promising results, with a 39-50% reduction in survival rates of malaria-carrying mosquitoes and elimination of 95% of Anopheles arabiensis mosquitoes in a bait station [113]. One of the most effective fungi studied recently against simultaneously Ae.…”
Section: Fungimentioning
confidence: 99%
“…Particular attention has been paid to fungal species belonging to the genera Lagenidium, Coelomomyces, Entomophthora, Culicinomyces, Beauveria, and Metarhizium for their power to reduce mosquito populations, but unfortunately, none of them have been specifically adapted as larvicidal agents against important vector species [109][110][111], even transgenic ones [112]. Application to surfaces on which mosquitoes land or need to pass through, such as fungus-impregnated cloths around bed nets, attractive bait stations, and adult mosquito traps and PET traps, show promising results, with a 39-50% reduction in survival rates of malaria-carrying mosquitoes and elimination of 95% of Anopheles arabiensis mosquitoes in a bait station [113]. One of the most effective fungi studied recently against simultaneously Ae.…”
Section: Fungimentioning
confidence: 99%
“…Mosquitoes can be controlled using entomopathogenic organisms such as fungi [76][77][78][79][80]. Although the role of blood meal in resistance to entomopathogenic fungi is unknown amongst mosquitoes, Cabral and co-workers indicated that Ae.…”
Section: Plos Onementioning
confidence: 99%
“…Por último, cabe destacar como modo de aplicación de hongos entomopatógenos, al uso de trampas para capturar e impregnar al mosquito (Lwetoijera et al, 2010;Snatselaar et al, 2014;Mmbando et al, 2015;Silva et al, 2018;Paula et al, 2018). Las mismas cuentan con la presencia de claves olfativas (dióxido de carbono, amonio y ácido carboxílico) y claves visuales (telas negras).…”
Section: Uso De Hongos Entomopatógenos Para El Control De Mosquitosunclassified
“…Los trabajos llevados a cabo con mosquitos mayoritariamente se enfocan en la aplicación indirecta de conidios de hongos entomopatógenos sobre papel (Scholte et al, 2007;Paula et al, 2008;Valero-Jimenez et al, 2014), telas (Mnyone et al, 2010(Mnyone et al, , 2012Farenhorst et al, 2011;Paula et al, 2013, Carolino et al, 2014, sustratos de arcilla o barro (Farenhorst et al, 2008;Mnyone et al, 2010), o bien, en el uso de trampas (Snetselaar et al, 2014;Silva et al, 2018;Paula et al, 2018). Si se piensa aplicar el producto a gran escala, la aplicación indirecta presenta ventajas sobre la directa tales como reducir el volumen a inocular, disminuir el contacto con el ser humano, y si se diseñan sustratos específicos para un determinado huésped, se puede disminuir la posibilidad de atacar a organismos no blancos o benéficos.…”
Section: Sustrato Con Cep 423unclassified
See 1 more Smart Citation